Coaching effectiveness in competitive youth contact sports and martial arts: athletes` and coaches` perceptions - Müjdeci, I.; Kiliç, K.; Bulut, A.; Kuru, H. (Frontiers in Psychology, 2026)
Background: Contact sports and martial arts can provide an avenue for young athletes` development in physical and psychosocial aspects. Athletes` consistent development of competence, confidence, connection, and character (the 4 Cs) are the desired athlete outcomes for optimal development in a defined sport context, reflecting the extent of coaching effectiveness and the quality of youth sport programming. The purpose of this study was to assess athletes` 4 Cs with respect to their age, gender, competitive level, and birthdate.